3D Porous cellulose/Si-Al inorganic polymer photonic film with precisely structure-enhanced solar reflectivity for daytime radiative cooling. (June 2022) - Liu, Chenghuan; Feng, Shuangjiang; He, Man; Chen, Xi; Shi, Shengnan; Bu, Xiaohai; Zhou, Yuming
Abstract: Porous structural polymer materials have the potential to achieve excellent passive daytime radiative cooling (PDRC). However, traditional porous polymer materials have irregularly internal structures that cannot effectively scatter sunlight, resulting in a low reflectivity in the solar spectrum. In this work, we designed a low-cost and eco-friendly structural film that transformed the cellulose acetate and Si-Al inorganic polymer particles into a regular three-dimensional (3D) network using the solvent exchange method. As a result, regularly distributed cavities with evenly size 3 µm self-formed with the leaving of solvent, which significantly enhanced the solar reflectance of the structural PDRC film to about 98%. Meanwhile, a high infrared emissivity in atmospheric window was also 83%. To prove the concept, the structural film was used for the outdoor PDRC process, and 6.56 ℃ cooling capacity could be produced even under the noon solar irradiance ( 1600 W/m 2 ) and sub-ambient temperature ( 34.6 ℃), as well as 2.38 ℃ below sub-ambient temperature at night. In addition, the mechanical strength and self-cleaning surface were integrated into the photonic film which extended its environment adaptability effectively. It was believed that this regularly porous strategy induced by, the hybrid of inorganic polymer would inspire the design of structural PDRC materials and the large-scale passive cooling technology. Graphical Abstract: ga1 Highlight: Regularly designed 3D network structure enhances the scattering efficiency of this cellulose-based film. Ultrahigh solar reflectance (98%) is achieved by randomly distributed air pores ( 3 µm). Self-cleaning capability and robust mechanical strength of the photonic extend its lifespan. 6.56 ℃ in daytime and 2.38 ℃ in nighttime cooling capacity have been achieved.